Report: A toolkit for PICSA facilitators - Bonilla, Melissa; Giraldo, Diana; Rios, David; Paez, Ana Maria; Diaz, Dilia (2025)
A human-centered design approach is developing a PICSA toolkit with clear instructions, worksheets, visual cards, and templates to reduce preparation burdens. Development follows five phases: Scope, Explore, Create, Validate, and Implement. The toolkit aims to enable genuine farmer participation, improve climate information comprehension, strengthen decision-making, and enhance agricultural resilience across Latin America and beyond. In this report we talk about how the Participatory Integrated Climate Services for Agriculture (PICSA) methodology effectively supports farmer decision-making, but facilitators in Latin America's dry corridor face significant implementation barriers: limited preparation time, inadequate materials, complex climate concepts, logistical constraints, and lack of context-appropriate tools. A needs assessment revealed that successful implementation depends heavily on practical resources, not just methodology. Challenges include conveying abstract climate concepts, disconnected steps, time constraints, insufficient engaging elements, limited portable materials, and language barriers. Without proper resources, participatory extension risks remaining extractive rather than transformative.